Effect of organic amendments on growth and yield attributes of medicinal and aromatic plants under peach-based agroforestry system in the mid-hills of the Western Himalayas. Issue 4 (1st October 2020) - Tripathi, Priyanka; Kashyap,; Shah, Shipra
ABSTRACT: The present study was conducted to assess the effect of organic manures on the growth and yield of three medicinal plant species ( Andrographis paniculata, Withania somnifera and Ocimum sanctum ) in an experimental peach-based agroforestry system. The experiment lasted 2 years. It was laid out in a Randomized Block Design with three replications each year, made up of 10 treatments for each medicinal plant at three different doses of vermicompost (2 t/ha, 4 t/ha, 6 t/ha) and three different doses of farmyard manure (15 t/ha, 20 t/ha, 25 t/ha) with or without peach trees. It was observed that the three species could successfully be cultivated as intercrops under peach without any adverse impact on their performance and production ability. Growth and yield attributes of MAPs were higher when intercropped under peach than under sole cropping system. The application of organic amendments had a significant effect on growth and yield of MAPs with superior performance at higher doses. This study emphasizes the potential of integrating medicinal plants in existing fruit-based systems as an efficient strategy for traditional farming communities in the Indian Himalayas to maximize land use efficiency and minimize resource degradation.